ANALYSIS OF OPERATING PARAMETERS ELECTRIC VEHICLES IN LOW TEMPERATURES - Муротбек Бойдадаев; Овлакулов Икром (Modern American Journals, 2025)
Currently, interest in electric vehicles continues to grow in the world, especially in Europe and America. Thus, the production of electric vehicles in the world increased from 240 thousand electric vehicles in 2013 to 400 thousand in 2014. And according to the forecast, sales of electric vehicles by 2024 will grow to 7.2 million electric vehicles. According to the forecast of the International Energy